1996
DOI: 10.1029/96gl01367
|View full text |Cite
|
Sign up to set email alerts
|

On blue jet dynamics

Abstract: A model is proposed for blue jets [Sentman and Wescott, 1995; Wescott et al., 1995a], which explains their dynamics, in particular the jet vertical velocity of about 100 km/s, the terminal altitudes of about 40–50 km, and the competitive occurrence of blue jets and the recently discovered blue starters [Wescott et al., 1995b]. A blue jet is considered to be formed by an attachment‐controlled ionizing wave, which moves upward via an electron avalanche in the wavefront due to the mainly vertical, downward direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…Earlier BJ theories included the runaway breakdown [ Roussel ‐ Dupré and Gurevich , 1996] and gigantic streamers of positive [ Pasko et al , 1996] and negative [ Sukhorukov et al , 1996] polarity. More rigorous analysis made by Petrov and Petrova [1999] came to the conclusion that BJs are formed by the streamer zone of a leader (streamer corona).…”
Section: Leader‐like Structure Of Blue Jetsmentioning
confidence: 99%
“…Earlier BJ theories included the runaway breakdown [ Roussel ‐ Dupré and Gurevich , 1996] and gigantic streamers of positive [ Pasko et al , 1996] and negative [ Sukhorukov et al , 1996] polarity. More rigorous analysis made by Petrov and Petrova [1999] came to the conclusion that BJs are formed by the streamer zone of a leader (streamer corona).…”
Section: Leader‐like Structure Of Blue Jetsmentioning
confidence: 99%
“…The first published theoretical models suggested that Jets are either gigantic positive streamers (Pasko et al, 1996) or negative streamers (Sukhorukov et al, 1996) produced by lightning discharges. The runaway breakdown model (Roussel-Dupre and Gurevich, 1996) also assumes that Jet brings a negative charge.…”
Section: Introductionmentioning
confidence: 99%
“…The streamers would have a concentration of positive charges at the front. Sukhorukov et al [1996] proposed negative streamers as the cause of jets but required a positive CG (+CG) flash to initiate the streamer. Roussel-Duprd et al [1998] 5.…”
Section: Introductionmentioning
confidence: 99%